Exploring How Accountability Affects the Medical Decisions We Make for Other People - Batteux, Eleonore; Ferguson, Eamonn; Tunney, Richard J. (Frontiers in Psychology, 2019)
In the event that a patient has lost their decision-making capacity due to illness or injury, a surrogate is often appointed to do so on their behalf. Research has shown that people take less risk when making treatment decisions for other people than they do for themselves. This has been discussed as surrogates employing greater caution for others given the accountability they are faced with. We tested the prediction that making accountability salient reduces risk- taking for others relative to the self by manipulating the information shown to participants while they made treatment choices. One group was asked to focus on the consequences for the recipient’s family, another on the legal implications of their decisions, and another was not given additional information. Participants reduced their risk-taking for others compared to themselves, irrespective of the condition they were in. Although participants in each condition reported thinking about these factors to different extents, there were no clear differences in risk-taking between groups. However, we did find that, across all participants, thinking about legal consequences reduces risk-taking. We suggest that future research investigates how the effect of thinking about accountability on surrogate choices is mediated by feelings of accountability, in order to further examine the explanations suggested in the literature.